Pyroclastic Stones as Building Materials in Medieval Romanesque Architecture of Sardinia (Italy): Chemical-Physical Features of Rocks and Associated Alterations. Issue 1 (2nd January 2022) - Columbu, Stefano; Palomba, M.; Sitzia, F.; Carcangiu, G.; Meloni, P.
ABSTRACT: The paper discusses the chemical-physical-petrographic features and decay processes of San Nicola Church (11 th −14 th century) building materials, one of the most representative Medieval Churches in Sardinia, stylistically attributable to the Romanesque architecture. The monument was built up into two stages and shows a characteristic size uniformity of the ashlars. The masonry is mainly made up of rhyodacitic pyroclastites belonging to the Sardinian Eocene-Miocene magmatic phase (38–15 My). These volcanic rocks were widely used in Medieval architecture for the excellent workability, but its minero-petrographic features greatly favor the decay, due to the action of chemical-physical alteration processes. Although the alteration degree and macroscopic forms of decay vary from zone to zone in the monument, according to the different compositional features of the volcanic stones, weathering and exposure condition, the pyroclastic rocks are generally affected by greater alteration than other igneous lithotypes, due to their petrographic-volcanological characteristics (e.g., low-medium welding grade, medium-high porosity). The results concerning mineralogical and petrographic features, respectively, carried out by the application of X-Ray Powder Diffraction (XRPD), Optical Microscope (OM), and Scanning Electron Microscope (SEM) techniques, both on fresh building rocks and associated alterations, are here presented and discussed. Furthermore, the relationships between fresh pyroclastites and alteration processes affecting these rocks will be discussed.